Understanding a Sentence Does Not Entail Knowing its Truth‐Conditions: Why the Epistemological Determination Argument Fails. (18th July 2013) - Cohnitz, Daniel; Kangilaski, Jaan
Abstract The determination argument is supposed to show that a sentence's meaning is at least a truth‐condition. This argument is supposed to rest on innocent premises that even a deflationist about truth can accept. The argument comes in two versions: one is metaphysical and the other is epistemological. In this paper we will focus on the epistemological version. We will argue that the apparently innocent first premise of that version of the argument is not as innocent as it seems. If the premise is understood in the sense required for the argument to go through then it should be rejected by a deflationist.